Principles and Constants of the Golden Proportion as a Criterion in Donosological Diagnostics of the Functional States of The Body and in the Assessment of the Probability of their Changes - M., Karabayev; N., M. Gasanova; M., T. Botirov; G.S., Kosimova (International Physiology Journal, 2022)
A theoretical paper proposes applications of golden proportion principles to physiological diagnostics. It outlines proposed metrics and discusses validation needs and limitations.
Keywords: functional state; adaptive potential; health levels; golden ratio constants; harmonization; optimization; assessment scale.